1986
DOI: 10.1007/bf01975915
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of fibronection to Teflon followed byS. aureus adherence

Abstract: Group B streptococcus can be a serious infection of neonates and, in the past, specific antibody has been shown to mediate immunity against this organism. However, specific antibody is not required for phagocytosis of highly pathogenic organisms by neutrophils. Furthermore, the bacteria subsequently survive and tend to accumulate or multiply in these cells, which they then disrupt. Highly pathogenic streptococci are killed by neutrophils in the presence of specific antibody. Moreover, the addition of specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

1990
1990
1990
1990

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…In contrast to these data, we [4,[8][9][10][11][12][13] and others [1,14,15] have found that plasma proteins strongly interfered with bacterial adhesion to polymer surfaces: indeed, the presence of either whole plasma [14] or serum [8,15], or of purified albumin [8][9][10][11][12][13] in the adhesion medium prevented staphylococcal adhesion to the native polymer surfaces. This serum protein-mediated inhibition of bacterial adhesion was observed with a range of different materials, such as PMMA [8,9,12,13], Teflon [10], fluorinated polyethylene-propylene films [14] and polyvinylchloride (PVC [11]) and with a number of clinical [12,14] and laboratory isolates [8][9][10][11]13] of staphylococci. Except for one study performed with tissue culture plates [111, we used for the others [8][9][10]12,13] a single type of in vitro experimental assay, which tested various staphylococcal strains for adhesion to small-sized polymer surfaces: coverslips (1 x 1 cm) made of either PUMA or ~flon were incubated in a shaking waterbath of 60 min at 37°C with calibrated suspensions of staphylococci containing generally 4 x 106 organisms/ml [8][9]…”
Section: Host Factors Influencing Staphylococcal Adhesion To I1~iplancontrasting
confidence: 67%
See 4 more Smart Citations
“…In contrast to these data, we [4,[8][9][10][11][12][13] and others [1,14,15] have found that plasma proteins strongly interfered with bacterial adhesion to polymer surfaces: indeed, the presence of either whole plasma [14] or serum [8,15], or of purified albumin [8][9][10][11][12][13] in the adhesion medium prevented staphylococcal adhesion to the native polymer surfaces. This serum protein-mediated inhibition of bacterial adhesion was observed with a range of different materials, such as PMMA [8,9,12,13], Teflon [10], fluorinated polyethylene-propylene films [14] and polyvinylchloride (PVC [11]) and with a number of clinical [12,14] and laboratory isolates [8][9][10][11]13] of staphylococci. Except for one study performed with tissue culture plates [111, we used for the others [8][9][10]12,13] a single type of in vitro experimental assay, which tested various staphylococcal strains for adhesion to small-sized polymer surfaces: coverslips (1 x 1 cm) made of either PUMA or ~flon were incubated in a shaking waterbath of 60 min at 37°C with calibrated suspensions of staphylococci containing generally 4 x 106 organisms/ml [8][9]…”
Section: Host Factors Influencing Staphylococcal Adhesion To I1~iplancontrasting
confidence: 67%
“…It is difficult to speculate from these in vitro data on the possible role in vivo of either surface-bound collagen or laminin as promoting directly staphylococcal adhesion. At least, we can say that collagen has an important role to play on staphylococcal adhesion as a cofactor, because it can promote adsorption of fibronectin on the surface of biomaterials [4,9,10]. Furthermore, fibronectin adsorbed on denatured collagen or gelatin layers shows an improved biological activity over fibronectin adsorbed on native polymers [4,9,10].…”
Section: Host Factors Influencing Staphylococcal Adhesion To I1~iplanmentioning
confidence: 98%
See 3 more Smart Citations